Fabrics of Indianness: The Exchange and Consumption of Clothing in Transnational Guyanese Hindu Communities - Kloß, Sinah Theres (Palgrave Macmillan, 2016)
This book describes how Guyanese Hindus recreate Indian ethnic identity in contemporary Guyana and examines how Hindu traditions have been transformed in this multi-religious and multi-ethnic society. By illustrating the exchange and consumption of clothing, the book demonstrates that the practices of wearing and gifting clothes materialize and visualize relationships. The significant outward migration of Guyanese to North America has resulted in substantial international gift exchange and transnational rituals. Applying the concept of translocality, this book demonstrates that different localities continue to influence transnational networks and socio-cultural practices. It provides a study of migration that emphasizes various aspects of material and visual closeness, conceptualizing the notion of touch
Keywords: Hochschulschrift; Ethnische Identität; Kleidung; Hindu; Inder; Guyana